Digital Readiness And Green Human Resource Management For Eco-Innovation In Indonesian Manufacturing - Alum Kusumah; Ronny Firdiansyah Arief; Sulistyandari Sulistyandari (Jurnal Minfo Polgan, 2025)
This study examines how digital readiness and green human resource management (GHRM) shape eco-innovation in Indonesian manufacturing firms. Survey data were collected from 300 senior managers across HR, operations, information technology and sustainability functions and analysed using partial least squares structural equation modelling (PLS-SEM). Digital readiness is positively related to eco-innovation (β=0.349) and to the implementation intensity of GHRM (β=0.364), while GHRM is positively associated with eco-innovation (β=0.345). Mediation analysis indicates that GHRM partially transmits the effect of digital readiness on eco-innovation (indirect β=0.126). The hypothesised moderating effects of environmental regulatory pressure and green organisational culture, and the digital readiness-GHRM interaction, are not supported. The findings position HRM as an integrative capability within the twin transition and suggest that firms can strengthen eco-innovation by aligning digital capability development with coherent green HR systems